IMPROVE THE CATALYTIC ACTIVITY OF FEOOH/BENTONITE MATERIAL BY MECHANICAL ACTIVATION - Guangtao Wei; Zhongmin Li; Linye Zhang; Yue Deng; Luhua Shao; Zihan Liu (Journal of the Chilean Chemical Society, 2017)
To improve the catalytic activity of FeOOH/bentonite material used in Fenton-like process, the activation of FeOOH/bentonite by mechanical activation was studied. The optimum conditions for activation of FeOOH/bentonite were as follows: filling ratio of grinding medium 30%, “15 mL of D06 balls plus 15 mL of D10 balls” as combination mode of grinding medium, rotation speed of planet carrier 600 rpm, milling time 40 min, and powder-to-ball ratio 0.5:30 (g·mL-1). The mechanical activation was an effective method to improve the catalytic activity of FeOOH/bentonite. Both the lattice distortion and crystal size decrease happened in α-FeOOH and the change of layer structure of bentonite were contributed to the increase of catalytic activity of activated FeOOH/bentonite.